2015
DOI: 10.1371/journal.pgen.1005509
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Dose-Controlled Regulation of Cellulase Gene Expression in Penicillium oxalicum

Abstract: Filamentous fungus Penicillium oxalicum produces diverse lignocellulolytic enzymes, which are regulated by the combinations of many transcription factors. Here, a single-gene disruptant library for 470 transcription factors was constructed and systematically screened for cellulase production. Twenty transcription factors (including ClrB, CreA, XlnR, Ace1, AmyR, and 15 unknown proteins) were identified to play putative roles in the activation or repression of cellulase synthesis. Most of these regulators have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
218
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(245 citation statements)
references
References 64 publications
13
218
1
2
Order By: Relevance
“…Aberrant expression of N. crassa CLR-2 through a constitutive promoter drives a nearly complete cellulase transcriptional response, even during growth on a normally repressive carbon source, indicating that CLR-2 does not require post-translational activation (Coradetti et al, 2013). This is not the case for other CLR-2 orthologs, however, since constitutive expression of A. nidulans and P. oxalicum ClrB does not result in constitutive activation of cellulolytic genes (Coradetti et al, 2013;Li et al, 2015). In N. crassa, regulation of clr-2 transcription is governed by a second zinc binuclear cluster transcription factor, CLR-1 .…”
Section: Primary Transcription Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Aberrant expression of N. crassa CLR-2 through a constitutive promoter drives a nearly complete cellulase transcriptional response, even during growth on a normally repressive carbon source, indicating that CLR-2 does not require post-translational activation (Coradetti et al, 2013). This is not the case for other CLR-2 orthologs, however, since constitutive expression of A. nidulans and P. oxalicum ClrB does not result in constitutive activation of cellulolytic genes (Coradetti et al, 2013;Li et al, 2015). In N. crassa, regulation of clr-2 transcription is governed by a second zinc binuclear cluster transcription factor, CLR-1 .…”
Section: Primary Transcription Factorsmentioning
confidence: 97%
“…In A. nidulans, CreA regulates xylanase genes as well as expression of their transcriptional regulator, xlnR (Orejas et al, 1999(Orejas et al, , 2001Tamayo et al, 2008). In N. crassa and P. oxalicum, regulation of cellulolytic genes as well as the transcription factor clr-2/clrB is thought to be under CCR control Li et al, 2015;Sun and Glass, 2011;Xiong et al, 2014b). Like in N. crassa and A. nidulans, in T. reesei, CRE1 regulates genes necessary for utilization of plant biomass as well as the transcription factors which regulate their expression.…”
mentioning
confidence: 99%
“…reesei, Aspergillus nidulans, N . crassa , and Penicillium oxalicum , such as the repressor CRE1/CreA (Strauss et al, 1995) and ACE1 (Aro et al, 2003) and the positive regulators XYR1/XlnR and CLR2/ClrB (Coradetti et al, 2012; Li et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The mechanism behind the regulation of lignocellulosic enzyme genes in P. oxalicum is similar to that in Aspergillus and Neurospora . Several transcription factors such as CreA (Liu et al, 2013a), ClrB, and XlnR (Li et al, 2015) have been found to play important roles in regulating cellulolytic enzyme gene expression. For instance, the overexpression of clrB , combined with both deletion of creA and an intracellular β-glucanse gene bgl2 , remarkably activated the cellulase gene expression and improved filter paper activity (FPA) by over 20-fold (Li et al, 2015; Yao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the degradation intensity of cellulase is depends on the transcription regulatory factor. ClrB is a global positive regulator,and ClrB/CLR -2, is essential for cellulase expression in P. oxalicum, N.crassa and Aspergillus nidulans [7,8] . It also belongs to the zinc finger protein transcription factor superfamily.…”
Section: Introductionmentioning
confidence: 99%